RELATION BETWEEN WEIGHT AND LINEAR MEASUREMENTS OF SHELL IN C. MADRASENSIS (PRESTON) - NAIR, N UNNIKRISHNAN; NAIR, N BALAKRISHNAN (Fishery Technology, 2017)
Relation of weight to height, length and breadth in the Indian backwater oyster Crassostrea madrasensis (Preston) is reported. The relative importance of the variables on weight was found to be height, length and breadth in their order of preference. The multiple regression V = -0.4017 + 0.46743 X + 0.8278 Y + 0.1130 Z can be used to estimate the meat weight (logarithm) for given dimensions of length, height and breadth (all in logarithms). An exponential relation between weight and height is also observed.